Gut Microbiota Diversity of Preterm Neonates Is Associated With Clostridioides Difficile Colonization - Jeanne Couturier; Jeanne Couturier; Patricia Lepage; Sarah Jolivet; Johanne Delannoy; Victoria Mesa; Pierre-Yves Ancel; Pierre-Yves Ancel; Jean-Christophe Rozé; Marie-José Butel; Frédéric Barbut; Frédéric Barbut; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In adults, Clostridioides difficile infections are associated with alterations of the intestinal bacterial populations. Although preterm neonates (PN) are frequently colonized by C. difficile, limited data are available regarding the relationship between C. difficile and the intestinal microbiota of this specific population. Therefore, we studied the intestinal microbiota of PN from two multicenter cohorts using high-throughput sequencing of the bacterial 16S rRNA gene. Our results showed that alpha diversity was significantly higher in children colonized by C. difficile than those without colonization. Beta diversity significantly differed between the groups. In multivariate analysis, C. difficile colonization was significantly associated with the absence of postnatal antibiotherapy and higher gestational age. Taxa belonging to the Lachnospiraceae, Enterobacteriaceae, Oscillospiraceae families and Veillonella sp. were positively associated with C. difficile colonization, whereas Bacteroidales and Bifidobacterium breve were negatively associated with C. difficile colonization. After adjustment for covariables, Clostridioides, Rothia, Bifidobacterium, Veillonella, Eisenbergiella genera and Enterobacterales were more abundant in the gut microbiota of colonized children. There was no significant association between C. difficile colonization and necrotizing enterocolitis in PN. Our results suggest that C. difficile colonization in PN is related to the establishment of physiological microbiota.